ANALISA DAMPAK BUNYI YANG DIHASILKAN OLEH BANDAR UDARA (BANDARA) SULTAN SYARIF KASIM II (SSK II) TERHADAP AMBANG PENDENGARAN SISWI SMK NEGERI PERTANIAN TERPADU PEKANBARU - Wahyuni, Reka; Retnowaty, Sri Fitria; Fitri, Yulia (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2013)
The airport of Sultan Syarif Kasim II Pekanbaru is the only one airport located in Pekanbaru city, Riau province and it is the media of air transportation that operates airplane. Sound intensity of plane could create the noisy that effect to psychological disturbance, physical disturbance and communicative disturbance. According to firmness of the head of ministry LH No.48/MENLH/11/1996 about standard quality of noisy level for environmental activities around school is 55 dBA. The objective of this study was to measure sound intensity at state vocational high school integrated agriculture Pekanbaru located at noisy area using Sound level meter digital and in order to find out its effect to the level of studentsâ auditory using Gurputala. On the results of research the intensity of sound obtained each day since Monday to Saturday was on average 69.46 dBA and the higher intensity was 93.1 dBA. And the results of inspection using garputala with 10 female students that for Rinne test 100% normal, but for Weber test 50% the students faced lateralization on right ear. And then for Schwbach the auditory of female students decreases. Thus, the attention of people and government is needed to overcome this problem, one of the ways is planting many trees at school environment and simple air proof in classroom. To obtain the score of auditory step it needs furthermore study using Audiometry to measure auditory step.